2016
DOI: 10.1111/jfd.12585
|View full text |Cite
|
Sign up to set email alerts
|

In vivo study of viral haemorrhagic septicaemia virus and infectious pancreatic necrosis virus coexistence in Senegalese sole (Solea senegalensis)

Abstract: The effect of IPNV-VHSV coinfection and superinfection on the mortality caused by both viruses in Senegalese sole has been analysed. No effect was observed after coinfection. However, a clear viral interference was recorded between a primary IPNV and a subsequent VHSV infection, which led to a survival increase in the infected sole of 50% points when compared with fish infected only with VHSV. The significantly higher Mx transcriptional values in the fish pre-exposed to IPNV (at least at first days after super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Alonso, Saint‐Jean, and Pérez‐Prieto () showed that inoculation with a mix of IPNV and IHNV resulted in a reduction in mortality rate (approximately 50% decrease) compared to an experimental infection with a single viral pathogen. Additionally, senegalese sole ( Solea senegalensis ) infected with IPNV followed by VHSV demonstrated viral interference via heightened protection, potentially via an increase in Mx gene expression (López‐Vázquez, Alonso, Dopazo, & Bandín, ). In Atlantic salmon, piscine orthoreovirus‐infected fish challenged with IHNV (genotype E) had enhanced survival against IHNV infection and showed decreased infection levels (Vendramin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Alonso, Saint‐Jean, and Pérez‐Prieto () showed that inoculation with a mix of IPNV and IHNV resulted in a reduction in mortality rate (approximately 50% decrease) compared to an experimental infection with a single viral pathogen. Additionally, senegalese sole ( Solea senegalensis ) infected with IPNV followed by VHSV demonstrated viral interference via heightened protection, potentially via an increase in Mx gene expression (López‐Vázquez, Alonso, Dopazo, & Bandín, ). In Atlantic salmon, piscine orthoreovirus‐infected fish challenged with IHNV (genotype E) had enhanced survival against IHNV infection and showed decreased infection levels (Vendramin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the titer of IPNV in our experiment was extremely high, the fish were in good health and the IPNV protected them from other virulent viruses. In this study we used the IPNV virus from genogroup V, but López-Vázquez et al also achieved good results [28] using the virus from genogroup I, and we still do not know what results would be obtained with IPNV from other genogroups with different virulence.…”
Section: Discussionmentioning
confidence: 89%
“…Co-infection was also studied by López-Vázquez et al and mortality reduction was also evident [28]. They studied the effect of IPNV+VHSV co-infection on the mortality caused by both viruses in Senegalese sole.…”
Section: Discussionmentioning
confidence: 94%
“…Many species of fish other than cyprinid and salmonid fish are known to be susceptible to ssRNA virus infections, also displaying a subsequent activation of the interferon pathway. In Pleuronectiformes (flatfish species), a potent induction of ifn and mx gene expression have been detected after challenge with rhabdoviruses HIRRV (hirame novirhabdovirus) and VHSV [ 64 , 65 , 66 , 67 , 68 ], with up to 16.000-fold increment of ifn levels at day 3 after VHSV infection. Likewise, high RNA expression levels of mx has been measured in the kidney and spleen of VHSV-infected perch [ 69 ].…”
Section: Ssrna Virusesmentioning
confidence: 99%